KINEMATICS ANALYSIS AND IMPLEMENTATION OF THREE DEGREES OF FREEDOM ROBOTIC ARM BY USING MATLAB (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
The kinematics modeling of the robot arm plays an important role in robot control. This paper presents the kinematic model of a three-degree of freedom articulated robot arm, which is designed for picking and placing an application with hand gripper, where a robot has been manufactured for that purpose. The forward kinematic model has been presented in order to determine the end effector’s poses using the Denavit-Hartenberg (DH) convention. For inverse kinematics, an algebraic solution based on trigonometric formulas mixed with geometric method was adopted for a 3 DOF modular manipulator taking into account the existence of a shoulder offset. MATLAB software was used as a tool to simulate and implement the motional characteristics of the robot arm, by creating a 3D visual software package under designing a Graphical User Interface "GUI" with a support simulation from robotic Toolbox (Rtb 10.3). Finally, an electronic interfacing circuit between the GUI program and the robot arm was developed using Arduino microcontroller to control the robot motion. The presented work can be applicable for learning the reality interface design methodology of the other kinds of robot manipulators and achieve a suitable solution for the motional characteristics